Enhancing entrepreneurship project-based learning for vocational schools with human-centered design and 3D printing - Noviyanti, Anastasia Ary; Saldi, Zaki Saptari; Prakasa, Danang Yudha; Santana, Fillberto Canvin; Akbar, M Fariz Salman (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Project-Based Learning (PBL) is vital for equipping Vocational High School (SMK) students with entrepreneurial skills to reduce unemployment. However, many schools face challenges in its effective implementation, particularly in integrating Industry 4.0 technologies. Contribution: This program introduced consumer-focused entrepreneurial thinking using Human-Centered Design (HCD) and 3D printing technology to teachers at SMKN 1 Pacet, Cianjur. Method: The initiative included workshops and a mini product development project. Effectiveness was evaluated through pre- and post-tests, prototype assessments, and reflective questionnaires. Results: Teachers' knowledge improved by 31%, with significant gains in skills and understanding. Conclusion: The program enhanced teachers' understanding of entrepreneurship PBL integrated with HCD and 3D printing, fostering innovative teaching approaches